That time I got reincarnated as a slime. 25 - Fuse (Manga author) (Kodansha Comics, 2024)
"The Tempest Founder's Festival has begun! Gathered in an uneasy truce, humans, demons and vampires explore the marvels of Rimuru's new kingdom: the concert hall, the technology, and even...Japanese food! But the grand event is the fighting tournament, where warriors of all lands test their skill, with ramifications that echo far beyond the arena. And among the challengers is Masayuki the Hero, the so-called Chosen One who might be stronger than the world's strongest slime..."--